Variables determining “Drop-By-Drop” Loan as a financing method - Lievano, Jhony Alexander Barrera; Ramirez, Sandra Miyey Parra; Mican, Edgar Olmedo Cruz; López, Juanita Ruíz (Edelweiss Applied Science and Technology, 2024)
Micro, small, and medium-sized enterprises - MSMEs are characterized by contributing significantly to nations’ economies worldwide, being dynamic agents of employment, supplying goods and services, and paying taxes. Among the factors that affect the sustainability and durability of these organizations is the financing to which they access the development of their activities. In Colombia, the figure of loans called "drop-by-drop" exists since illegality, which due to its characteristics generates problems of sustainability and growth for MSMEs that access them. This research was carried out to determine if there is a linear relationship between variables associated with access to loans "drop-by-drop". It was developed under a quantitative, correlational, non-experimental, and transactional approach. We worked with a probabilistic sample. As the main findings, it was obtained that between the analysis variables, there is a correlation at different levels; In the same way, it was possible to identify two particular phenomena, the first, is that more than 50% of MSMEs have access to credits neither with the formal nor with the informal financial sector, the second, that those that access financing with the informal system are They submit to the conditions imposed by the lenders, among which are high interest rates and putting their businesses, their families and even their lives at risk. The main conclusion is the need to create financing products from the formal actors of the country’s financial system, which responds to the needs of MSMEs since an unattended potential market is evident.